Flame-retardant regenerated polyester fiber for new energy automobile battery pack and preparation method thereof

CN122959879APending Publication Date: 2026-10-23GUANGDONG YUANHUI ENVIRONMENTAL PROTECTION FIBER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611217953.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-12
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,再生聚酯回收料的阻燃性能仍存在不足

Benefits of technology

本发明制得的无卤协效阻燃改性料是通过使用负载钼酸铵的介孔载体为核,以氨苯砜有机层为壳制得。首先,交联氨苯砜有机层含有极性的砜基和芳环结构,与聚酯基体具有良好的界面亲和性,能够有效改善无机介孔填料与有机聚酯之间的界面相容性,避免填料团聚,保障熔融纺丝过程的连续稳定性与可纺性。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the technical field of polyester fibers, and discloses a flame-retardant regenerated polyester fiber for new energy automobile battery packs and a preparation method thereof. The regenerated polyester fiber is prepared from regenerated polyester scraps, polyethylene wax, halogen-free synergistic flame-retardant modified material and antioxidants through mixing, extrusion and melt spinning processes. The halogen-free synergistic flame-retardant modified material is prepared by using a mesoporous carrier loaded with ammonium molybdate as a core and a crosslinked sulfonamide organic layer as a shell. The presence of the crosslinked sulfonamide organic layer can improve the interfacial compatibility between the inorganic mesoporous filler and the organic polyester, compensate for the mechanical property degradation of the regenerated polyester caused by repeated processing or the presence of impurities, and improve the tensile strength of the fiber. In the combustion process, the ammonium molybdate loaded in the mesoporous channel releases molybdenum oxide, which synergizes with the crosslinked sulfonamide organic layer to improve the flame-retardant properties of the regenerated polyester fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyester fiber technology, specifically to a flame-retardant recycled polyester fiber for new energy vehicle battery packs and its preparation method. Background Technology

[0002] With the rapid development of the new energy vehicle industry, the safety of power battery systems has received increasing attention. As a core component of new energy vehicles, the battery pack's thermal runaway protection is a crucial aspect of ensuring overall vehicle safety. Once thermal runaway occurs inside the battery pack, heat accumulates rapidly and may trigger a chain reaction in adjacent cells. Therefore, protective materials with flame-retardant and heat-insulating functions are needed in critical locations such as between battery modules and on top of the cells. Currently, fire-resistant materials for battery packs mainly consist of fire-resistant felt materials, such as mica sheets, ultrafine glass wool, and high-silica felt. However, these traditional inorganic fire-resistant materials suffer from problems such as heavy weight, insufficient flexibility, and limited processing performance, making it difficult to meet the requirements of new energy vehicles for lightweight design and adaptability to complex shapes.

[0003] Polyester fiber possesses excellent properties such as high strength, good abrasion resistance, and dimensional stability, and is widely used in the automotive industry for interior materials and industrial textiles. Flame-retardant polyester staple fiber, through modification technology, can achieve high limiting oxygen index, low smoke emission, and difficult ignition, while also exhibiting long-lasting flame retardant effects that are non-toxic, non-corrosive, and pollution-free. In recent years, polyester spunbond nonwoven materials have shown application potential in battery pack safety systems. However, existing flame-retardant polyester fiber products mainly use virgin polyester as raw material, resulting in high production costs, and the extensive use of virgin petrochemical resources is inconsistent with the green and low-carbon development trend.

[0004] On the other hand, with the continuous growth of global polyester production, the pollution problem caused by waste polyester products is becoming increasingly serious. Recycled polyester fiber, using waste polyester bottles, waste textiles, and spinning waste liquid as raw materials, has significant advantages such as low raw material costs, resource recycling, and environmental friendliness. Recycled polyester is now widely used in clothing, automotive trim, packaging, and other fields. However, the flame retardant properties of recycled polyester materials still have shortcomings.

[0005] In view of this, developing a flame-retardant recycled polyester fiber specifically for new energy vehicle battery packs, possessing both excellent flame-retardant properties and good mechanical properties, and its preparation method, is of great significance for realizing the high-value utilization of waste polyester resources, improving the safety protection level of battery packs, and promoting the green development of the new energy vehicle industry. Summary of the Invention

[0006] In order to solve the problems mentioned in the background art, the purpose of this invention is to provide a flame-retardant recycled polyester fiber for new energy vehicle battery packs and a method for preparing the same.

[0007] The objective of this invention can be achieved through the following technical solutions: A flame-retardant recycled polyester fiber for new energy vehicle battery packs, comprising the following raw materials by weight: Recycled polyester scraps: 82-95 parts; Polyethylene wax: 1-3 parts; Halogen-free synergistic flame retardant modifier: 3-6.8 parts; Antioxidant: 0.3-0.5 parts.

[0008] As a further aspect of the present invention, the preparation method of the halogen-free synergistic flame retardant modifier includes the following steps: Step 1: Add the mesoporous carrier to deionized water and disperse it evenly. Then add ammonium heptamolybdate tetrahydrate to the resulting dispersion, stir well, and treat it at an ultrasonic frequency of 100-120kHz for 2-4 hours to form a mixture. Step 2: Dissolve sulfamic acid in N,N-dimethylformamide to prepare a modification solution; add the modification solution dropwise to the mixture, stir for 20-40 minutes after addition, continue to add crosslinking agent, keep warm at 60-70℃ and stir for 4-8 hours, cool down and discharge the material, wash and dry the collected solid material.

[0009] As a further aspect of the present invention, the mesoporous carrier is prepared by the following method: Add hexadecyltrimethylammonium bromide to an ethanol solution and stir to dissolve. Then add tetraethyl orthosilicate and stir for 20-30 minutes. Next, add calcium nitrate tetrahydrate and triethyl phosphate, and adjust the pH. Continue stirring for 4-6 hours, then let it stand for 24-48 hours to form a gel. After drying, place it in a muffle furnace and control the heating rate to 1-2℃ / min. Raise the temperature to 550-600℃ and remove it after 2-4 hours.

[0010] As a further aspect of the present invention, the volume fraction of the ethanol solution is 60-70%.

[0011] As a further embodiment of the present invention, the pH is 2-4.

[0012] As a further aspect of the present invention, the mass ratio of the mesoporous carrier to ammonium heptamolybdate tetrahydrate is 1:0.1-0.2.

[0013] As a further aspect of the present invention, the crosslinking agent is polyethylene glycol diglycidyl ether.

[0014] As a further aspect of the present invention, the number-average molecular weight of the polyethylene glycol diglycidyl ether is 2000.

[0015] As a further aspect of the present invention, the antioxidant is any one of antioxidant 1010, antioxidant 168, or antioxidant 1076.

[0016] In the above technical solution, it should be noted that, firstly, a mesoporous carrier is prepared by template method. The cavitation effect of high-frequency ultrasound is used to overcome the liquid phase diffusion resistance, allowing ammonium molybdate to be fully impregnated and filled into the mesoporous channels. Then, sulfamic acid is added, and its amino groups are adsorbed onto the inner and outer surfaces of the channels by hydrogen bonding with the silanol groups on the carrier surface. Finally, a crosslinking agent is added to cause the adsorbed sulfamic acid to undergo interfacial polymerization, forming a dense crosslinked polymer thin layer on the carrier surface. This thin layer not only plays a synergistic role in flame retardancy, but also acts as a physical barrier to effectively encapsulate ammonium molybdate in the channels, preventing the active components from being released, thereby obtaining a structurally stable halogen-free synergistic flame retardant modified material.

[0017] A method for preparing flame-retardant recycled polyester fiber for new energy vehicle battery packs includes the following steps: The first step is to crush the waste polyester into recycled polyester scrap. The second step involves adding recycled polyester scraps, polyethylene wax, halogen-free synergistic flame retardant modifier, and antioxidant into a mixer, mechanically mixing them evenly, and then feeding them into a twin-screw extruder for melt granulation to form polyester masterbatch. The third step is to melt-spin the masterbatch, cool it into filaments by side blowing, and then stretch the resulting nascent fibers by airflow.

[0018] The beneficial effects of this invention are: The halogen-free synergistic flame-retardant modified material prepared by this invention is obtained by using a mesoporous carrier loaded with ammonium molybdate as the core and an aminophenyl sulfone organic layer as the shell. First, the cross-linked aminophenyl sulfone organic layer contains polar sulfone groups and aromatic ring structures, which have good interfacial affinity with the polyester matrix. It can effectively improve the interfacial compatibility between inorganic mesoporous fillers and organic polyesters, avoid filler agglomeration, and ensure the continuous stability and spinnability of the melt spinning process.

[0019] Secondly, the uniformly dispersed mesoporous carrier, as rigid nanoparticles, plays a role in physical cross-linking and stress dispersion of the recycled polyester matrix, which can compensate for the deterioration of mechanical properties caused by repeated processing or the presence of impurities in the recycled polyester and improve the tensile strength of the fiber.

[0020] Furthermore, ammonium molybdate loaded within the mesoporous channels releases molybdenum oxide during combustion, which promotes the dehydrogenation and cross-linking of polyester into char. Through redox reactions, it converts incompletely burned carbon particles into carbon dioxide. Meanwhile, the cross-linked sulfone organic layer decomposes upon heating, producing inert gases containing nitrogen and sulfur, which dilute the concentration of combustible gases and further promote the formation of a dense char layer. Simultaneously, under high-temperature combustion conditions, molybdenum oxide reacts with silicon oxide on the mesoporous carrier to produce molybdate silicates, which can improve the strength of the char layer. The synergistic effect of molybdenum, nitrogen, and silicon endows the fiber with excellent flame-retardant properties. At the same time, the cross-linked shell structure effectively delays the thermal migration and precipitation of ammonium molybdate during processing and use, ensuring the durability of the flame-retardant effect and processing stability.

[0021] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Detailed Implementation

[0022] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0023] Example 1 This embodiment provides a flame-retardant recycled polyester fiber for new energy vehicle battery packs, comprising the following raw materials by mass parts: Recycled polyester scraps: 82 parts; Polyethylene wax: 1 part; Halogen-free synergistic flame retardant modifier: 3 parts; Antioxidant 1010: 0.3 parts.

[0024] The method for preparing the recycled polyester fiber includes the following steps: The first step is to crush the recycled polyester staple fiber into recycled polyester scrap with a particle size of 0.1-0.5mm; The second step involves adding recycled polyester scraps, polyethylene wax, halogen-free synergistic flame retardant modifier, and antioxidant 1010 into a mixer, mechanically mixing them evenly, and then feeding them into a twin-screw extruder for melt granulation to form polyester masterbatch. The third step involves controlling the spinning temperature at 260℃ and the spinning rate at 1000m / min to melt-spin the masterbatch, cooling it into filaments by side blowing, and then stretching the resulting nascent fibers by airflow at a stretching speed of 0.8MPa and 5000m / min.

[0025] The recycled polyester staple fiber was purchased from Yangzhou Rongcheng Chemical Fiber Co., Ltd., and the same applies below.

[0026] The preparation method of the halogen-free synergistic flame retardant modified material includes the following steps: Step A: Add 5g of cetyltrimethylammonium bromide to a 60% (v / v) ethanol solution, stir to dissolve, then add 1.3g of tetraethyl orthosilicate. After the addition is complete, stir for 30 minutes, then add 1.5g of calcium nitrate tetrahydrate and 0.15g of triethyl phosphate, adjust the pH to 2, and continue stirring for 5 hours. After standing and aging for 36 hours, a gel will form. After drying, place it in a muffle furnace, control the heating rate at 1℃ / min, raise the temperature to 550℃, and remove it after 3 hours. Step B: Add 1.5g of mesoporous support to 10mL of deionized water, disperse evenly, add 0.3g of ammonium heptamolybdate tetrahydrate to the dispersion, stir evenly, and treat with ultrasound at 100kHz for 3h to form a mixture. Step C: Dissolve sulfamic acid in N,N-dimethylformamide to prepare a 5% (w / w) modification solution; add 10 mL of the modification solution dropwise to the mixture, stir for 30 min after addition, then add 4 g of polyethylene glycol diglycidyl ether with a number average molecular weight of 2000, keep warm and stir at 70℃ for 6 h, cool down and discharge the material, wash and dry the collected solid material.

[0027] Example 2 This embodiment provides a flame-retardant recycled polyester fiber for new energy vehicle battery packs, comprising the following raw materials by mass parts: Recycled polyester scraps: 85 parts; Polyethylene wax: 2 parts; Halogen-free synergistic flame retardant modifier: 6 parts; Antioxidant 1010: 0.4 parts.

[0028] The method for preparing the recycled polyester fiber includes the following steps: The first step is to crush the recycled polyester staple fiber into recycled polyester scrap with a particle size of 0.1-0.5mm; The second step involves adding recycled polyester scraps, polyethylene wax, halogen-free synergistic flame retardant modifier, and antioxidant 1010 into a mixer, mechanically mixing them evenly, and then feeding them into a twin-screw extruder for melt granulation to form polyester masterbatch. The third step involves controlling the spinning temperature at 260℃ and the spinning rate at 1000m / min to melt-spin the masterbatch, cooling it into filaments by side blowing, and then stretching the resulting nascent fibers by airflow at a stretching speed of 0.8MPa and 5000m / min.

[0029] The preparation method of the halogen-free synergistic flame retardant modified material is the same as that in Example 1.

[0030] Example 3 This embodiment provides a flame-retardant recycled polyester fiber for new energy vehicle battery packs, comprising the following raw materials by mass parts: Recycled polyester scraps: 95 parts; Polyethylene wax: 3 parts; Halogen-free synergistic flame retardant modifier: 6.8 parts; Antioxidant 1010: 0.5 parts.

[0031] The method for preparing the recycled polyester fiber includes the following steps: The first step is to crush the recycled polyester staple fiber into recycled polyester scrap with a particle size of 0.1-0.5mm; The second step involves adding recycled polyester scraps, polyethylene wax, halogen-free synergistic flame retardant modifier, and antioxidant 1010 into a mixer, mechanically mixing them evenly, and then feeding them into a twin-screw extruder for melt granulation to form polyester masterbatch. The third step involves controlling the spinning temperature at 260℃ and the spinning rate at 1000m / min to melt-spin the masterbatch, cooling it into filaments by side blowing, and then stretching the resulting nascent fibers by airflow at a stretching speed of 0.8MPa and 5000m / min.

[0032] The preparation method of the halogen-free synergistic flame retardant modified material is the same as that in Example 1.

[0033] Comparative Example 1 This comparative example provides a recycled polyester fiber, which differs from Example 2 in that the halogen-free synergistic flame retardant modifier is replaced with a mixture of mesoporous carrier and ammonium molybdate in a mass ratio of 5:1, while all other aspects are the same.

[0034] The preparation method of the mesoporous carrier is described in Example 1.

[0035] Comparative Example 2 This comparative example provides a recycled polyester fiber, which differs from Example 2 in that the halogen-free synergistic flame retardant modifier is replaced with a mesoporous carrier, while the rest are the same.

[0036] The preparation method of the mesoporous carrier is described in Example 1.

[0037] Comparative Example 3 This comparative example provides a recycled polyester fiber, which differs from Example 2 in that the halogen-free synergistic flame retardant modifier is replaced with ammonium molybdate, while the rest are the same.

[0038] Comparative Example 4 This comparative example provides a recycled polyester fiber, which differs from Example 2 in that the halogen-free synergistic flame retardant modifier is replaced with a carrier mixture, while the rest are the same.

[0039] The method for preparing the carrier mixture includes the following steps: Step A: Add 5g of cetyltrimethylammonium bromide to a 60% (v / v) ethanol solution, stir to dissolve, then add 1.3g of tetraethyl orthosilicate. After the addition is complete, stir for 30 minutes, then add 1.5g of calcium nitrate tetrahydrate and 0.15g of triethyl phosphate, adjust the pH to 2, and continue stirring for 5 hours. After standing and aging for 36 hours, a gel will form. After drying, place it in a muffle furnace, control the heating rate at 1℃ / min, raise the temperature to 550℃, and remove it after 3 hours. Step B: Add 1.5g of mesoporous support to 10mL of deionized water, disperse evenly, add 0.3g of ammonium heptamolybdate tetrahydrate to the dispersion, stir evenly, and treat with ultrasound at 100kHz for 3h to form a mixture. Step C: Dissolve sulfamic acid in N,N-dimethylformamide to prepare a 5% (w / w) modification solution; add 10 mL of the modification solution dropwise to the mixture, stir for 30 min after addition, and discharge the material. Wash and dry the collected solid material to obtain the carrier mixture.

[0040] Comparative Example 5 This comparative example provides a recycled polyester fiber, which differs from Example 2 in that the halogen-free synergistic flame retardant modifier is removed, while the rest are the same.

[0041] Test case Various performance tests were conducted on the recycled polyester fibers used in the above embodiments and comparative examples, and the results are recorded in the table below: Table 1 - Test Results Fracture strength (cN / detx) Limiting oxygen index (%) Example 1 5.74 30.2 Example 2 5.85 30.6 Example 3 5.81 30.5 Comparative Example 1 4.49 27.1 Comparative Example 2 4.82 26.0 Comparative Example 3 4.01 27.8 Comparative Example 4 5.68 28.9 Comparative Example 5 3.94 19.7 The tensile strength test was conducted using an XL-1 multifilament tensile strength tester. The limiting oxygen index is tested according to standard GB / T 8924-2005 by twisting recycled polyester fibers into strip samples with a diameter of (6.5±0.5) mm and a length of 100 mm. Test results show that recycled polyester fibers prepared with halogen-free synergistic flame retardant modifiers exhibit good mechanical strength and flame retardant properties. However, when the halogen-free synergistic flame retardant modifiers are replaced with a mixture of mesoporous carrier and ammonium molybdate, the ammonium molybdate may migrate during processing, and the advantages of the cross-linked sulfamic acid organic layer are lost, leading to varying degrees of decline in both the mechanical and flame retardant properties of the recycled polyester fibers. Furthermore, replacing the halogen-free synergistic flame retardant modifiers with mesoporous carriers further eliminates the flame retardant effect of ammonium molybdate, resulting in an even further decrease in the flame retardant properties of the recycled polyester fibers.

[0042] Replacing the halogen-free synergistic flame retardant modifier with ammonium molybdate results in the loss of the reinforcing advantage of the mesoporous carrier, leading to a further reduction in the mechanical strength of the polyester fiber.

[0043] Using a carrier mixture with an uncrosslinked surface as an additive, ammonium molybdate may undergo thermal migration during processing, resulting in slightly poorer flame retardant properties of the fiber.

[0044] This document uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of these embodiments are merely to aid in understanding the method and core ideas of the present invention, including the best mode, and to enable any person skilled in the art to practice the present invention, including manufacturing and using any device or system, and implementing any combined method. It should be noted that those skilled in the art can make various improvements and modifications to the present invention without departing from its principles, and these improvements and modifications also fall within the scope of protection of the claims. The scope of protection of this patent is defined by the claims and may include other embodiments that can be conceived by those skilled in the art. If these other embodiments have structural elements similar to those expressed in the claims, or if they include equivalent structural elements that are not substantially different from those expressed in the claims, then these other embodiments should also be included within the scope of the claims.

[0045] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A flame-retardant recycled polyester fiber for new energy vehicle battery packs, characterized in that, Measured by mass parts, including the following raw materials: Recycled polyester scraps: 82-95 parts; Polyethylene wax: 1-3 parts; Halogen-free synergistic flame retardant modifier: 3-6.8 parts; Antioxidant: 0.3-0.5 parts.

2. The flame-retardant recycled polyester fiber for new energy vehicle battery packs according to claim 1, characterized in that, The preparation method of the halogen-free synergistic flame retardant modified material includes the following steps: Step 1: Add the mesoporous carrier to deionized water and disperse it evenly. Then add ammonium heptamolybdate tetrahydrate to the resulting dispersion, stir well, and treat it at an ultrasonic frequency of 100-120kHz for 2-4 hours to form a mixture. Step 2: Dissolve sulfamic acid in N,N-dimethylformamide to prepare a modification solution; add the modification solution dropwise to the mixture, stir for 20-40 minutes after addition, continue to add crosslinking agent, keep warm at 60-70℃ and stir for 4-8 hours, cool down and discharge the material, wash and dry the collected solid material.

3. The flame-retardant recycled polyester fiber for new energy vehicle battery packs according to claim 2, characterized in that, The mesoporous support is prepared using the following method: Add hexadecyltrimethylammonium bromide to an ethanol solution and stir to dissolve. Then add tetraethyl orthosilicate and stir for 20-30 minutes. Next, add calcium nitrate tetrahydrate and triethyl phosphate, and adjust the pH. Continue stirring for 4-6 hours, then let it stand for 24-48 hours to form a gel. After drying, place it in a muffle furnace and control the heating rate to 1-2℃ / min. Raise the temperature to 550-600℃ and remove it after 2-4 hours.

4. The flame-retardant recycled polyester fiber for new energy vehicle battery packs according to claim 3, characterized in that, The volume fraction of the ethanol solution is 60-70%.

5. The flame-retardant recycled polyester fiber for new energy vehicle battery packs according to claim 3, characterized in that, The pH is 2-4.

6. The flame-retardant recycled polyester fiber for new energy vehicle battery packs according to claim 2, characterized in that, The mass ratio of the mesoporous carrier to ammonium heptamolybdate tetrahydrate is 1:0.1-0.

2.

7. The flame-retardant recycled polyester fiber for new energy vehicle battery packs according to claim 2, characterized in that, The crosslinking agent is polyethylene glycol diglycidyl ether.

8. The flame-retardant recycled polyester fiber for new energy vehicle battery packs according to claim 7, characterized in that, The number-average molecular weight of the polyethylene glycol diglycidyl ether is 2000.

9. The flame-retardant recycled polyester fiber for new energy vehicle battery packs according to claim 1, characterized in that, The antioxidant is any one of antioxidant 1010, antioxidant 168, or antioxidant 1076.

10. A method for preparing flame-retardant recycled polyester fiber for new energy vehicle battery packs as described in claim 1, characterized in that, Includes the following steps: The first step is to crush the waste polyester into recycled polyester scrap. The second step involves adding recycled polyester scraps, polyethylene wax, halogen-free synergistic flame retardant modifier, and antioxidant into a mixer, mechanically mixing them evenly, and then feeding them into a twin-screw extruder for melt granulation to form polyester masterbatch. The third step is to melt-spin the masterbatch, cool it into filaments by side blowing, and then stretch the resulting nascent fibers by airflow.